S.M.A.K. 07/08. - Van Cauteren, Philippe (Gent : SMAK (Stedelijk Museum voor Actuele Kunst) Gent, 2009)
Henning, Anton ; Geers, Kendell ; McCarthy, Paul ; Bijl, Guillaume ; Garabedian, Mekhitar ; Broodthaers, Marcel ; Wenzel, Anne ; Rogiers, Peter ; Geys, Jef ; Manders, Mark ; Mannaers, Werner ; Morellet, François ; Herold, Georg ; Hugonnier, Marine ; Just, Jesper ; Alimpiev, Victor ; Martin, Daria ; Thurnauer, Agnès ; Lodewijks, Bart ; Krauss, Clemens ; Volckaert, T.M.C. ; Persoons, Leen ; Westphal, Sarah ; Liugov, Boris ; Roffare, Carlo ; Roncade, Arno ; Prieto, Wilfredo ; de Velde, Rinus Van ; Sudhues, Max ; Beckmann, Matthias ; Dörner, Michael ; Huyghe, Philip ; Leech, Adam ; Melsheimer, Isa ; Solleveld, Aam ; Van Ingelgem, Herman ; Vandekerckhove, Hans ; Kuivila, Ron ; van der Heide, Edwin ; Broodthaers, Marcel ; François, Michel ; Panamarenko ; Zorio, Gilberto ; Beuys, Joseph ; Dheedene, Stefaan ; Geyskens, Vincent ; Hirakawa, Noritoshi ; Gelper, Johan ; Pasaiko, Oksana ; Timmermans, Ante ; Sasnal, Wilhelm ; Bertrand, Gaston ; De Keyser, Raoul ; Fabre, Jan ; Maes, Ives ; Solakov, Nedko ; De Wilde, Johan ; Hanssen, Karin ; Kit, Lee ; Visch, Henk ; Vermeersch, Pieter ; Gerhard, Tatjana ; Vanderheyden, JCJ ; Ingridmwangiroberthutter ; Dierickx, Karel ; Birnbaum, Dara ; Eguchi, Saturo ; Nuur, Navid ; Ervinck, Nick ; De Keyzer, Carl ; Scherubel, Klaus ; Buedts, Raphaël
Nederlands
boek